Tlingit potlatch dancers in costume at potlatch, Klukwan, Alaska, 1898 - Hegg, Eric A., 1867-1948
Men in beaded and embroidered shirts, hats and headdresses, ca. 1897-1900. They have painted faces, hold feathers or carved staffs, and several wear noserings. Behind them is a tent and a carved poles. Caption on image: 602. Costumes worn at potlatch, Klukwan, Alaska. E. A. Hegg